Millennial's perspective of clicker technology in a nursing classroom: A Mixed methods research study - Toothaker, Rebecca (Nurse education today, 2018)
Nursing education is facing challenges and a shift in paradigm within the nursing classroom. Educators need to explore innovative strategies that engage students. Clickers are one tool that can enhance participation, protect anonymity, and promote learning of concepts. This mixed methods study evaluated nursing student's perceptions of clicker technology during lecture. This study uses a 9-item questionnaire to explore perceived levels of student perception of the technology of clickers in a nursing classroom. The sample consisted of ninety-nine sophomore and senior level nursing students. Participants were recruited using convenience sampling. Ninety-one percent of the students agreed or strongly agreed that the use of clickers helped them to develop a better understanding of the subject matter when compared to traditional lecture based class. The findings portray a positive correlation of learning and an enhanced pedagogical approach for nursing students. •The use of clickers reveals a positive correlation of learning and enhanced pedagogical approach.•Millennials desire active pedagogies in the classroom.•Engagement of learners is essential to the millennial generation.•Clicker technology promotes learning of key concepts.